Kisah Israiliyyat dalam Tafsir Perspektif Ibnu Khaldun Pada Kitab al-Muqaddimah - Muhtarul Alif (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
This article discusses Israeliyyat's stories in Ibn Khaldun's perspective on the Muqaddimah book. Ibn Khaldun is an Islamic historian who is called the father of historiography, the father of economics, and also the father of sociology who has a monumental work entitled Muqaddimah. The thoughts of Ibn Khaldun are important treasures in unraveling various problems, including Israeliyyat's stories. Israeliyyat's stories is part of the ad-dakhil fi al-tafsir that reaps pro and contra. Studies of al-dakhil fi al-tafsir have been carried out by many scholars, which are generally carried out through a historical validation approach with a small portion of rational validation. Ibn Khaldun in his Muqaddimah criticizes Israeliyyat's stories which he thinks are contrary to common sense. The purpose of this study is to unravel Ibn Khaldun's critique of israeliyyat's stories in the Muqaddimah. The method used in this study is qualitative research by examining specifically the thoughts of Ibn Khaldun related to israeliyyat's stories in Muqaddimah accompanied by various other references from the book of interpretation. Then, the data is presented in an analytical descriptive manner. The results of this study are that the causes of the inclusion of the israiliyyat story are the lack of critical investigation of data sources, lack of practical knowledge about political principles, socio-cultural society and also ignoring the dynamics of social change of a nation. Therefore, the results of this study are very important in revealing the depth of Ibn Khaldun's thinking, especially concerning the criticism of Israeliyyat's stories.